The History of Economic Thought : After Keynes, Through the Great Recession and Beyond. - Ashford, Robert (Business law collection., 2017)
The subject of this book is the history of economic thought, including the less-commonly discussed schools of binary and socio-economics. Readers will benefit by coming away from the book with a better understanding of the context within which economic arguments are made. -- Provided by publisher.